"I'm the One Who Pieces Back Together What Was Broken": Uncovering Mestiza Consciousness in Latina-Identified First-Generation College Student Narratives of Stress and Coping in Higher Education. Issue 2 (3rd May 2020) - Espino, Michelle M.
Abstract : This study uncovers how 15 Latina-identified first-generation college students draw from mestiza consciousness to develop coping strategies for navigating multiple worlds of family, community, and higher education. The findings suggest that Latina-identified first-generation college students develop mestiza consciousness by (a) (un)consciously drawing from their strengths, (b) reframing their academic experiences even amid struggle through self-talk, and (c) drawing knowledge and motivation from their own selves and, at times, from family and trained therapists. By attending to the fragmentation that occurs from tensions experienced by Latina-identified first-generation college students, colleges and universities can offer support for them to leverage their ways of knowing and succeed in higher education.